Comparison of quality and early postoperative complications between Laparascopy and Laparotomy in 112 women undergoing tubal ligation - S Arefi (JRI, 2000)
The aim of this study was to evaluate the quality, effective ness and the ideal method of tubal ligation with low complication, low bleeding and early recovery. In this investigation we compared the early complications and the quality of operations in two different tubul ligation techniqwes on totally 112 women who were operated in two centers in Tehran, Iran; In one group (53 women ) tubal ligation was carried out by laparascopy (with clips and cautery, whereas the other group (59 women) was operated using Pomeroy technique in laparotomy. Collection of information was done using questionare and case selection and grouping was performed randomly. The results showed that the duration of operation and hospitalization as well as the amount of bleeding were less in laparascopy group than in laparatomy group (P<0.05). Moreover, women in laparascopy group could completely retain their activity more rapidly than the other group. Hematoma and infection were only slightly higher in patients in laparatomy group (P>0.05), whereas pain occurred more aften in the laparatomy group (P<0.05). It can be concluded that complications occur less often in the laparascopy goup in compoarison with lapartony goup and tubal ligation with laparascopy can be considerd as a better and safer method.
Keywords: Tubal Ligation, Laparascopy, Pomeroy, Laparatomy, Clips, Couterization